LITERATURE REVIEW : PENGARUH EDUKASI KESEHATAN TERHADAP PENINGKATAN PERILAKU HIDUP SEHAT PADA REMAJA - Hunafa Fitria Ningrum; Larasati; Laurencia Meilinda Putri; Wahyudi (PT. Hasba Edukasi Mandiri, 2025)
Adolescence is a vulnerable phase to lifestyle influences, one of which is the habit of consuming fast food (junk food), which can have a negative impact on health. Health education plays a crucial role in increasing adolescents' knowledge and awareness of the importance of healthy eating. This article uses a literature review method to describe research findings that examine the influence of health education on adolescents' healthy lifestyle behaviors, particularly in dietary aspects. Articles were collected from Google Scholar, PubMed, and ScienceDirect with a publication year range of 2021–2025. Inclusion criteria included articles in both Indonesian and English that discussed health education and adolescent lifestyle behaviors. Exclusion criteria included articles that were irrelevant to the topic, were opinion pieces or editorials, lacked clear methods and results, were not available in full text, or were published outside the publication year range. Based on the review results, health education has been proven effective in improving adolescents' knowledge, attitudes, and behaviors in reducing junk food consumption and establishing healthier eating habits from an early age.